MENINGKATKAN HASIL BELAJAR Pakat DAN GOTONG ROYONG MELALUI MODEL DISCOVERY LEARNING FASE A SD NEGERI LEBO - Herlina Bong (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Herlina Bong. The objectives of this Class Action Research are a). To determine the improvement of learning outcomes through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. b). To determine the increase in the dimension of mutual assistance through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. c). To determine the increase in achievement targets through the Discovery Learning model for grade II Phase A students of SD Negeri Lebo. Action Research class consists of 2 cycles, each cycle consists of four stages, namely: planning, implementation, observation and reflection. The subjects of the study were grade II students of SD Negeri Lebo totaling 6 people, consisting of 2 men and 4 women. The object of research is the result of learning and the mutual assistance of students in the study of Catholic Religion and Ethics on the material